Effects of exercise training on heart rate variability in individuals with lower extremity arterial disease and claudication: A systematic review - Marçal, Isabela R. [UNESP]; Abreu, Raphael M.; Cornelis, Nils; Leicht, Anthony S.; Forjaz, Claudia L.M.; Cucato, Gabriel; Brenner, Ingrid; Novakovic, Marko; Ritti-Dias, Raphael; Ciolac, Emmanuel G. [UNESP]; Cornelissen, Véronique A. (Elsevier, 2023)
Purpose: To perform a systematic review of studies assessing the effects of regular exercise on heart rate variability (HRV) in individuals with lower extremity arterial disease (LEAD) and symptoms of claudication. Methods: A systematic search in the electronic databases MEDLINE, Embase, and Scielo, was conducted and updated on January 21, 2023. Randomized clinical trials investigating patients with LEAD and IC, assessing ≥ 4 wk of exercise interventions, and reporting at least one HRV measure (e.g., time or frequency domains) at baseline and follow-up were included. Two reviewers independently screened studies for inclusion, performed data extraction, and quality assessment of included studies. Results: Data from 7 trials were included (i.e., 5 walking, 1 resistance, and 1 isometric handgrip training), totaling 327 patients (66% males; range: 61 - 68 yr; ankle brachial index: 0.4 - 0.7). Following exercise training, three studies investigating walking training reported an increase in parasympathetic modulation indices and/or a decrease in sympathetic modulation indices (n = 2) as well as an increase in non-linear indices (n = 1). Conclusion: The current evidence is weak, and larger randomized controlled trials are needed to confirm the efficacy of exercise training in improving HRV. Additionally, the high divergence in the methodology of studies indicated the need for standard tools to improve the quality of HRV measurements in exercise trials. It is recommended to use standard procedures in future trials investigating HRV.
Keywords: Autonomic function; Peripheral arterial disease; Strength training; Walking therapy